Biodiversity, Agrobiodiversity and Ecosystem Change - Girot Pignot, Pascal Oliver (2011)
Biodiversity is the variety of life, in all its forms. It provides the foods and medicines used around the world today, the fiber for clothes, and many of the materials for shelter and houses, and a plethora of other goods and services such as soil nutrients, clean water, disease and climate buffering, energy and much else, which sustains livelihoods of millions of rural poor, and on which all people are ultimately dependent. As such biodiversity is a critical element of human security. Biodiversity loss particularly affects the poor, who are most directly dependent on ecosystem services at the local scale. Loss of access to biological resources, and the increasing erosion of agrobiodiversity limit future options for development, resulting in many cases in the exacerbation of vulnerability of the poor. Ultimately, biodiversity loss represents a source of risk, as unfraying ecosystems impact livelihoods and human health and provide less protection in extremes events involving wind, ocean waves, flooding, drought, and movement of slopes, amongst others. The mitigation of biodiversity loss can be achieved through in-situ and ex-situ conservation, through protected areas or botanical gardens, seed banks and other top down approaches. Meanwhile, bottom-up approaches are increasingly emerging as an important option for limiting biodiversity loss, through community forestry, collaborative management of protected areas and other activities that contribute to the sustainable use of biodiversity, and to creating resilient livelihoods that reduce vulnerability through incorporating biodiversity into production landscapes.